Discovering Camphill: a personal narrative - Thom Garfat (Scottish Journal of Residential Child Care)
Recently the author was invited to visit Camphill School, Aberdeen, to reflect on his experience of the Camphill programme in light of contemporary thinking about 'best environments' for young people with serious learning disabilities. At the end of his experience of 'discovering Camphill' for himself, the author was invited to share his experiences with the participants invited to a one-day conference organised by the school in Aberdeen. This paper is a representation of what the author had to say as he reflected on his personal experience of 'discovering Camphill'.